2022
DOI: 10.3390/diagnostics12112611
|View full text |Cite
|
Sign up to set email alerts
|

Commercially Available Molecular Approaches to Evaluate Endometrial Receptivity: A Systematic Review and Critical Analysis of the Literature

Abstract: Despite the advances in the field of reproductive medicine, implantation failure represents a challenging condition affecting 10–30% of patients subjected to in vitro fertilization (IVF). Research has focused on the identification of molecules playing crucial roles in endometrial receptivity, with the aim of designing predictive tools for efficient detection of the implantation window. To that end, novel molecular genomic and transcriptomic approaches have been introduced as promising tools to enable personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Given the increasing deeper understanding in the transcriptomic characterization of the endometrial cycle, up- and downregulated genes deciphering the molecular features of a receptive endometrium and endometrial receptivity were recently identified ( 32 , 33 ). Thus, different molecular predictive tools were designed and established to evaluate endometrial receptivity status and predict the optimal WOI, aiming to optimize embryo transfer timing ( 34 ). Win-Test (window implantation test) was developed in 2009 by Haouzi et al based on the expression levels of 11 genes determined by qRT-PCR to predict the receptive endometrial status and revealed improved clinical outcomes of RIF patients after pET compared to patients undergoing standard ET ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing deeper understanding in the transcriptomic characterization of the endometrial cycle, up- and downregulated genes deciphering the molecular features of a receptive endometrium and endometrial receptivity were recently identified ( 32 , 33 ). Thus, different molecular predictive tools were designed and established to evaluate endometrial receptivity status and predict the optimal WOI, aiming to optimize embryo transfer timing ( 34 ). Win-Test (window implantation test) was developed in 2009 by Haouzi et al based on the expression levels of 11 genes determined by qRT-PCR to predict the receptive endometrial status and revealed improved clinical outcomes of RIF patients after pET compared to patients undergoing standard ET ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies focusing on embryo competence and endometrial status have been conducted [ 2 ], and it has been established that a good-quality embryo, a receptive endometrium and an effective dialogue between them are required to achieve pregnancy [ 1 ]. The timing of ET, which can take place from day two to day seven post oocyte fertilization, is critical for the success of implantation [ 3 ], and the debate and reasoning behind each option are dynamically discussed in the literature [ 4 , 5 ], while molecular data have been argued to be useful in indicating the optimal ET day within the menstrual cycle, albeit a more personalized approach seems to be required [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the improvement of IVF techniques and preimplantation genetic testing (PGT) to assess embryo euploidy, implantation failure remains a challenge. Approximately 10–30% of patients referred to IVF clinics experience implantation failure [ 2 ], and attention has been focused on measures to improve pregnancy outcomes. Among these, the identification of difficult procedures of embryo transfer [ 3 ], methods of creating optimal embryo cultures [ 4 , 5 ], the standardization of morphological criteria to classify blastocyst competency [ 6 , 7 ], the improvement of PGT [ 8 ], and measures to identify the optimal day for embryo transfer [ 9 , 10 , 11 ], have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In a 28-day normal cycle, the WOI occurs around 6–10 days after the LH surge and lasts about 3–6 days [ 14 , 16 , 17 ]. In cases of artificial cycles, the WOI occurs 4–7 days after the administration of progesterone [ 2 ]. The WOI is finely regulated by a plethora of factors, which include hormones, such as estrogen and progesterone, cytokines, and growth and immunomodulatory factors, all driving a series of morphological and molecular changes fundamental for a correct blastocyst-endometrial dialogue.…”
Section: Introductionmentioning
confidence: 99%